The Impact of Strategic Trajectory Optimization on Illusory Target Biases During Goal-Directed Aiming. Issue 6 (1st November 2016) - Roberts, James W.; Burkitt, James J.; Elliott, Digby; Lyons, James L.
ABSTRACT: During rapid aiming, movements are planned and executed to avoid worst-case outcomes that require time and energy to correct. As such, downward movements initially undershoot the target to avoid corrections against gravity. Illusory target context can also impact aiming bias. Here, the authors sought to determine how strategic biases mediate illusory biases. Participants aimed to Müller-Lyer figures in different directions (forward, backward, up, down). Downward biases emerged late in the movement and illusory biases emerged from peak velocity. The illusory effects were greater for downward movements at terminal endpoint. These results indicate that strategic biases interact with the limb-target control processes associated with illusory biases. Thus, multiple control processes during rapid aiming may combine and later affect endpoint accuracy (D. Elliott et al., 2010 ).